Analisis Pengembangan Bahan Ajar Ekonomi dengan App Inventor2 Terhadap Kemandirian Belajar - Majdi, Muhammad Zainul; Rizkiwati, Baiq Yuliana (Universitas Hamzanwadi, 2018)
The development of technology has penetrated to various aspects of life including in the field of education. Teachers have been using technology to facilitate the learning process that aims to improve the quality of education. These conditions underlie the conduct of various studies related to learning technology. This study aims to develop teaching materials on economic subjects by using APP INVENTOR2 then the development results are used to analyze student learning independence. As research development or Research and Development (R & D), this research uses ADDIE development model which consists of five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation ), and 5) Evaluation. From these five stages, this study only reached the fourth stage and did not perform the fifth stage of evaluation phase.The result of the analysis shows that the level of feasibility of APP INVENTOR2 teaching materials based on the expert material's appraisal is very good category, the expert of the teaching materials with the excellent category and the economic learning practitioners with very good category. Student learning independence on average shows a high degree of independence ≥ 70%. Meanwhile, for the students response to the teaching materials when tested on average showed a positive response with a percentage of ≥ 70% on each indicator. Thus the development of teaching materials on economic subjects with APP INVENTOR2 is feasible to use.